STATUS KEBERLANJUTAN LAHAN SAWAH DI KABUPATEN TABANAN - A.A.A. Wulandira Sawitri Djelantik; Made Sudiana Sudiana Mahendra; Wayan Windia; Made Sudarma (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
The conversion of paddy fields that occurred in Tabanan district has caused concern because the number continues to increase every year. Of the various forms of agricultural land use, paddy fields are land that has undergone many changes in designation so that the conversion of paddy fields occurs rapidly and massively. The total area of ??paddy fields that decreased in the 5 years from 2016 to 2020 was 1,193.54 hectares. Seeing this phenomenon, it is important to know how the status of rice fields in Tabanan Regency is sustainable using five dimensions, namely economy, ecology, social, technology and institutional. The data were obtained through interviews with Pekaseh (kelihan subak) and farmers who carried out the conversion of paddy fields in nine subaks in nine sub-districts in Tabanan Regency, namely Pupuan, Penebel, Baturiti, Kediri, Tabanan, Kerambitan, Selemadeg, West Selemadeg, and East Selemadeg Districts. The analysis used is MDS (Multi Dimension Scaling) which is an adjustment of Rapfish using RSI TM Software (Rapid Sustainability Index) which was developed for the assessment of sustainability functions in general. The results showed that the multi-dimensional sustainability index obtained a value of 59.70 with a moderately sustainable sustainability status with the index value for each dimension being 74.56 for the ecological dimension with moderately sustainable status, 48.82 for the economic dimension with less sustainable status, 75.42 for the social dimension with sustainable status, 52.43 for the institutional dimension with moderately sustainable status and 47.25 for the technological dimension with less sustainable status. It is suggested that the local government of Tabanan Regency should to pay attention to the attributes that exist in the economic and technological dimensions so that it is expected to change its sustainability status to be quite sustainable, or sustainable and the attributes that exist in the ecological and institutional dimensions (sufficiently sustainable) can shift its status to continyu so that the value of the multi-dimensional index can increase. Keywords: conversion; paddy fields; sustainability status